Fuel reformulation in the Metropolitan Area of Mexico City. (1st January 2002) - Diaz, L.; Avalos, S.; Schifter, I.; Vera, M.; Castillo, M.; Rodriguez, R.; Larios, P.; Lopez-Salinas, E.; Gamas, E.
The Metropolitan Area of Mexico City (MAMC) is the urban area of the country, which presents the most critical environmental problem due to fuel consumption. In an attempt to reduce the ambient concentration of pollutants, the environmental programme adopted by the Metropolitan Environmental Commission consisted of a broad series of strategies. Fuel modifications, which include changing the composition and physical properties, provide a particularly effective way to reduce emissions. The reformulated fuels in Mexico, one Regular type and the other Premium, have a reduced aromatics content (from 300 to 250 ml/l), fewer olefins (from 150 to 100 ml/l) and less benzene (from 20 to 10 ml/l), as well as a reduction in the Reid vapour pressure from 8.5 to 7.8 psi (0.60 to 0.55 kg/cm²). This paper presents experimental results about the behaviour of representative vehicles of the actual fleet in the MAMC, tested with both fuels. The regulated emissions, carbon monoxide, total hydrocarbons and nitrogen oxides, were evaluated for each vehicle and also the individual hydrocarbons present in the exhaust emission. With these data, it was possible to estimate the potential reactivity of the fuels to generate ozone and also to correlate the results with the technology of the vehicles. Data are correlated with previous work done in the United States.